Staging women's lives in academia : gendered life stages in language and literature workplaces - Massé, Michelle A. (Michelle Annette), 1951-; Maglin, Nan Bauer (Albany : State University of New York Press, 2017)
"Argues that institutional change must accommodate women's professional and personal life stages. Staging Women's Lives in Academia demonstrates how ostensibly personal decisions are shaped by institutions and advocates for ways that workplaces, not women, must be changed. Addressing life stages ranging from graduate school through retirement, these essays represent a gamut of institutions and women who draw upon both personal experience and scholarly expertise. The contributors contemplate the slipperiness of the very categories we construct to explain the stages of life and ask key questions, such as what does it mean to be a graduate student at fifty? Or a full professor at thirty-five? The book explores the ways women in all stages of academia feel that they are always too young or too old, too attentive to work or too overly focused on family. By including the voices of those who leave, as well as those who stay, this collection signals the need to rebuild the house of academia so that women can have not only classrooms of their own but also lives of their own"--Provided by publisher.
Part I. Graduate School. 1. A Job That Gets Old Fast: Age Studies, Academic Labor Criticism, and the Graduate Employee -- 2. Discourse of Aspiration: A Community of Nontraditional Women Students -- 3. The Accidental Academic, or How to Succeed in Academia through Failure and Doubt -- 4. Uses of My Anger: Negotiating Mothering, Feminism, and Graduate School -- 5. The Chaos of Kairos: Conflicting Discourses of Timing, Mothering, and Flexibility -- Part II. Early Career (Including Pre-Tenure). 6. Working-Class Women on the Tenure Track -- 7. My Double Life in Academia, or Extreme Parenting on the Tenure Track -- 8. Solo on Stage: The Single Mother's Solitary Path to Tenure -- 9. Square Peg, Round Hole: My Journey toward Professor of Practice -- 10. Currency -- 11. Settling Down without Settling: Reflecting on Ambition, Agency, and Acquiescence -- Part III. Midcareer (Including Post-Tenure). 12. Lives Like Mine: Notes at Midlife on Career Change -- 13. The Good Enough Academic Mother at Midcareer -- 14. Solitary in the South: Confessions of a Single Academic at Midlife -- 15. (In)Visibilities: A Woman Faculty of Color's Search for a Disabled Identity That Fits -- 16. Voicing Discontent: Gender, Working-Class Values, and Composition Studies -- 17. Staging Women's Lives on the "Altac" Track -- 18. Gratitude, Agency, and the Reformation of the Stage Approach -- Part IV. Late Career and Retirement. 19. The Academic Slow Lane -- 20. Relentless Improvising: A Full Professor Struggles to Manage Work, Family, and Health -- 21. An Academic Evolution: From Chicanita to Mamá to Abuela -- 22. Love's Labors: Taking Care of Mother -- 23. A View of Her Own -- 24. The Work of Retirement -- 25. Retirement in Two Voices.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Women college teachers -- Professional relationships -- United States; Women college teachers -- United States -- Social conditions; Women in higher education -- Social conditions; Women -- Education (Graduate) -- United States; Women graduate students -- United States -- Social conditions; Women college graduates -- Employment -- United States; Professeures (Enseignement supérieur) -- États-Unis -- Conditions sociales; Femmes dans l'enseignement supérieur -- Conditions sociales; Femmes -- Enseignement des 2e et 3e cycles -- États-Unis.; EDUCATION -- Higher; Women college graduates -- Employment; Women college teachers -- Social conditions; Women -- Education (Graduate); Women graduate students -- Social conditions; United States